Room temperature ionic liquid promoted improved and rapid synthesis of 2,4,5-triaryl imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone - Siddiqui, S. A.; Narkhede, U. C.; Palimkar, S. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Tetrahedron, 2005)
An improved and rapid one-pot synthesis of 2,4,5-triaryl imidazoles in a room temperature ionic liquid is described, which does not need any added catalyst. Different ionic liquids based on 1-n-butyl and 1,3-di-n-butyl imidazolium salts were screened and their efficacy in terms of acidity and polarity have been correlated with yields and reaction period. The one-pot methodology resulting in excellent isolated yields in short reaction times is characterized by simple work up procedures and efficient recovery and recycling of the ionic liquid, which acts as a promoter. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 2-Diketones; 4; 5-triaryl imidazoles; alpha-hydroxyketone; ammonium acetate; benzaldehydes; ionic liquid (IL)

Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
6th International Conference on Solvothermal Reactions, Mysore, INDIA, AUG 24-27, 2004
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts